2019
DOI: 10.1093/braincomms/fcz037
|View full text |Cite
|
Sign up to set email alerts
|

Sustained involuntary muscle activity in cerebral palsy and stroke: same symptom, diverse mechanisms

Abstract: Abstract Individuals with lesions of central motor pathways frequently suffer from sustained involuntary muscle activity. This symptom shares clinical characteristics with dystonia but is observable in individuals classified as spastic. The term spastic dystonia has been introduced, although the underlying mechanisms of involuntary activity are not clarified and vary between individuals depending on the disorder. This study aimed to investigate the nature and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…As a result, IMA was characterized by low or exceedingly low RMS levels with much higher peak-to-peak amplitudes. The presence of few long-lasting trains of MUs is in line with the results obtained by both Campanini and colleagues in acute patients with UMNL evaluated in similar conditions using a linear array of electrodes [ 7 ], and by Mottram et al and Forman et al in chronic patients [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…As a result, IMA was characterized by low or exceedingly low RMS levels with much higher peak-to-peak amplitudes. The presence of few long-lasting trains of MUs is in line with the results obtained by both Campanini and colleagues in acute patients with UMNL evaluated in similar conditions using a linear array of electrodes [ 7 ], and by Mottram et al and Forman et al in chronic patients [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 87%
“…In a study by Trompetto et al, IMA was found in the flexor carpi radialis muscle at rest in 17 patients, out of the 23 evaluated chronic stroke patients [ 9 ]. In a study by Forman et al, eight out of eight chronic stroke patients presented IMA in the biceps brachii when the muscle was extended [ 8 ]. This phenomenon was seen in chronic patients, who presented an increased resistance to passive movement and a clinically assessed spasticity (modified Ashworth scale score ≥ 1) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations